Legal Protection Of Children In Mixed Marriages In Indonesia - Fuspitasari, Nova; Maryano, Maryano; Somajaipeng , Kacha (CV. Era Digital Nusantara, 2024)
This research aims to analyse the legal protection of children from mixed marriages in Indonesia, focusing on the issue of citizenship and basic rights of children. In the context of Indonesian law, the citizenship of children of mixed marriages is often an issue of legal uncertainty, impacting on children's inheritance rights, education, health and social welfare. Although Indonesia has a legal basis that provides for limited dual citizenship for children of mixed marriages, the implementation of the existing law still faces challenges, including unclear procedures, lack of socialisation, and uncertainty in inheritance and parenting rights. This study concludes that the government's efforts to provide legal protection have been made, but there are still legal loopholes that jeopardise children's rights. Therefore, it is recommended that the government strengthen the implementation of the law, conduct more intensive socialisation, and formulate more specific regulations to protect the rights of children in mixed marriages. This research provides a scientific contribution in understanding the dynamics of child rights protection in Indonesia, especially in the context of dual citizenship, and provides policy recommendations for improving the Indonesian legal system.